A novel derivative of the prosthetic group heme d1: S-methylporphyrindione d1 - Timkovich, Russell; Carlin, Richard T. (Biochimica et biophysica acta, 1992)
Several derivatives of heme d 1 have been characterized by ultraviolet-visible, NMR, and mass spectrometry. Most arise from side reactions during the isolation of d 1 from the enzyme. One, however, has now been shown to correspond to the replacement of a meso proton by an S-methyl group. Since the prophyrin is not exposed to S-methyl-containing agents during its isolation, this raises hypotheses that it has its origin in vivo.